Microscopy of bacterial translocation during small bowel obstruction and ischemia in vivo: a new animal model - Samel, Stephan Tim; Keese, Michael; Groove-Kleczka, Martha; Lanig, Sybille; Gretz, Norbert; Hafner, Mathias; Sturm, Jörg; Post, Stefan (BMC surgery, 2002)
Existing animal models provide only indirect information about the pathogenesis of infections caused by indigenous gastrointestinal microflora and the kinetics of bacterial translocation. The aim of this study was to develop a novel animal model to assess bacterial translocation and intestinal barrier function in vivo.
Gesehen am 24.06.2022